Late-Onset Ileocutaneous Fistula Eight Years After Plug Repair With Polypropylene Mesh: A Case Report - Zhang, Jiankang; Hu, Zeming; Lin, Xuan; Chen, Bin (Frontiers in Surgery, 2021)
Introduction: As one of the short-term complications after inguinal hernia repair, mesh infection frequently occurs but rarely leads to ileocutaneous fistula. We present a rare case of ileocutaneous fistula eight years after inguinal hernia plug repair with polypropylene mesh. Case Presentation: The patient was a 67-year-old male who underwent a plug repair with polypropylene mesh of the right inguinal hernia. Eight years after the primary repair, skin ulceration with pus presented in the right groin area, and the final diagnosis was enterocutaneous fistula. According to laparoscopic exploration, the ileum below the fistula closely adhered to the abdominal wall. After gently separating the bowel loop, a defect area of about 2 cm×3 cm was observed on the surface of the ileum. In laparotomy, the mesh was found embedded in the ileum and then was completely removed, and an ileum side-to-side anastomosis was performed. The patient was discharged two weeks after the surgery, and follow-up at the sixth month revealed complete healing of the wound and no evidence of hernia recurrence. Conclusion: Late-onset ileocutaneous fistula should be considered in the differential diagnosis in patients who present inflammation and abscess formation after hernia repair. Besides, for patients with suspected intestinal fistula after hernia repair, laparoscopic exploration should be given priority, and the mesh removal approach should be tailored according to the results of laparoscopic exploration.